Pengembangan Panduan Menulis Teks Laporan Hasil Observasi Outdoor Learning Siswa Kelas V SD Muhammadiyah 16 Surabaya - Mulyadi, Agus; Sujinah, Sujinah; Yarno, Yarno (Universitas Islam Sumatera Utara, 2025)
This study aims to develop a writing guide for observation report texts tailored to outdoor learning activities, integrating both observational and writing components to support students in composing structured and coherent reports. Employing the Research and Development (RD) methodology, the study follows a series of phases: analysis, design, development, implementation, and evaluation. Validation was conducted through assessments by both experts and users. The validation results demonstrate a high level of feasibility, with expert and user approval ratings of 97% and 96.16%, respectively, yielding an average of 96.58%, which is categorized as “very good.” These findings indicate that the developed guide significantly contributes to the improvement of students’ writing competencies in the context of outdoor learning. Consequently, the guide proves to be an effective instructional tool to enhance the quality of observation-based writing in primary education, particularly at SD Muhammadiyah 16 Surabaya.